2004
DOI: 10.1523/jneurosci.3720-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Specific Na+Sensors Are Functionally Expressed in a Neuronal Population of the Median Preoptic Nucleus of the Rat

Abstract: ] out exclusively. The specific Na ϩ response was voltage insensitive and depended on the driving force for Na ϩ ions, indicating that a sustained background Na ϩ permeability controlled the membrane potential of the MnPO neurons. This specific response was not reduced by Gd 3ϩ , amiloride, or benzamil, ruling out the participation of mechanosensitive cationic channels, specific epithelial Na ϩ channels, and Phe-Met-Arg-Phe-gated Na ϩ channels, respectively. Combination of in situ hybridization, using a ribopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 38 publications
8
64
0
Order By: Relevance
“…MnPO neurons have previously been shown to respond to exogenous ANG II by a sustained depolarization (3,36). To reconcile these data with the present results, we introduced an identification criterion for neurons displaying ANG II-mediated modulation of the GABA A response, i.e., sensitivity to a change in ambient Na ϩ level (14). Our results indicated that all neurons displaying either the (Sar 1 , Ile 8 )-ANG II-induced reduction in eIPSCs (n ϭ 5) or the ANG II-induced facilitation of the muscimol-activated GABA A /Cl Ϫ current (n ϭ 6) also responded to local application of isoosmotic-hyponatriuric aCSF (300 mOsm/l, 100 mM NaCl; 1 min) with a membrane hyperpolarization of 7 Ϯ 0.9 mV (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…MnPO neurons have previously been shown to respond to exogenous ANG II by a sustained depolarization (3,36). To reconcile these data with the present results, we introduced an identification criterion for neurons displaying ANG II-mediated modulation of the GABA A response, i.e., sensitivity to a change in ambient Na ϩ level (14). Our results indicated that all neurons displaying either the (Sar 1 , Ile 8 )-ANG II-induced reduction in eIPSCs (n ϭ 5) or the ANG II-induced facilitation of the muscimol-activated GABA A /Cl Ϫ current (n ϭ 6) also responded to local application of isoosmotic-hyponatriuric aCSF (300 mOsm/l, 100 mM NaCl; 1 min) with a membrane hyperpolarization of 7 Ϯ 0.9 mV (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Changes in plasma osmolality have been shown to alter the spiking activity of MnPO neurons (1,29,37,38), and our laboratory discovered that these changes in electrical activity of MnPO neurons were driven by changes in the cerebrospinal fluid (CSF) Na ϩ level, rather than CSF osmolality (14). Behavioral studies showed that ANG II infused into the OVLT or adjacent MnPO caused an increase in Na ϩ intake (8,10,11).…”
mentioning
confidence: 99%
“…Indeed, although hypertonic NaCl can elicit excitatory responses from OVLT neurons in brain slices even when they are perfused with low Ca 2ϩ solutions to block synaptic transmission (Vivas et al, 1990), such experiments do not exclude a possible role for substances released from nonneuronal osmosensory cells or the involvement of Na ϩ receptors rather than osmoreceptors. Indeed, recent studies have demonstrated that osmotically regulated taurine release by glial cells can contribute to neuronal osmoresponsiveness through the activation of glycine receptors (Hussy, 2002), and subpopulations of neurons in the lamina terminalis have been shown to be specifically sensitive to changes in sodium concentration rather than osmolality (Grob et al, 2004). Our finding that isolated OVLT neurons respond to solutions made hypertonic via the addition of mannitol therefore provide the first direct evidence that a large proportion of these cells are intrinsically osmosensitive.…”
Section: Ovlt Neurons Are Intrinsically Osmosensitivesupporting
confidence: 52%
“…A second possibility is that CNS areas other than the OVLT can contribute to the osmotic modulation of thirst. Indeed, osmosensitive and Na ϩ -sensitive neurons have been found in the subfornical organ (Anderson et al, 2001) and in the median preoptic nucleus (McAllen et al, 1990;Travis and Johnson, 1993;Grob et al, 2004), areas known to be part of the integrated neural circuit that underlies osmoregulation (Johnson and Gross, 1993). Finally, it is possible that our protocol did not lead to a pure osmotic stimulus and that additional (i.e., non-osmotic) factors contributed to the thirst response.…”
Section: Impaired Osmotic Thirst In Trpv1mentioning
confidence: 97%
“…A gene that was persistently upregulated was the Scn6a, an atypical sodium channel gene that serves as a sodium-level sensor of the body fluid (Hiyama et al, 2002;Watanabe et al, 2006). This gene was originally considered to be a glial sodium channel (Gautron et al, 1992), although neuronal localization has also been observed (Grob et al, 2004). The persistent increased expression was the more remarkable because expression of other sodium channel subunits was reduced.…”
Section: Glia and Ion Homeostasismentioning
confidence: 99%